2020
DOI: 10.3390/su12072836
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Element Modelling of Rubber-Protected Ballast Performance Subjected to Direct Shear Test and Cyclic Loading

Abstract: The rubber-protected ballast (RPB) is made from natural ballast particles and crumb rubber particles. The crumb rubber is shredded waste tires. RPB was chosen to replace the ballast as it has higher resistance to breakage and abrasion. However, the static and dynamic performance of the RPB has not been confirmed yet. Towards this end, experimental tests and numerical simulations were utilized to study the feasibility of RPB application. Direct shear tests (DSTs) were performed and a DST model and three-sleeper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 51 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…In accordance with conducted research by Sol-Sánchez et al, Coating aggregates with crumb rubber smaller than 0.5 mm reduced long-term settlement and damping [2]. The study of the shear properties of these materials by Guo et al has shown that the use of ballast with rubber coating decreased the shear strength and stiffness of the track, but the use of 0-0.025 mm rubber particles caused less reduction in these two parameters [3] In the literature, the effect of rubber coating on ballast life has not been considered. Therefore, in this study, after selecting the best method for creating rubber coating on ballast aggregates, the effect of using this material on increasing the lifespan of materials was studied by performing Los Angeles and Micro-Daval experiments.…”
supporting
confidence: 80%
“…In accordance with conducted research by Sol-Sánchez et al, Coating aggregates with crumb rubber smaller than 0.5 mm reduced long-term settlement and damping [2]. The study of the shear properties of these materials by Guo et al has shown that the use of ballast with rubber coating decreased the shear strength and stiffness of the track, but the use of 0-0.025 mm rubber particles caused less reduction in these two parameters [3] In the literature, the effect of rubber coating on ballast life has not been considered. Therefore, in this study, after selecting the best method for creating rubber coating on ballast aggregates, the effect of using this material on increasing the lifespan of materials was studied by performing Los Angeles and Micro-Daval experiments.…”
supporting
confidence: 80%
“…Gravel is connected to the two particles and is randomly located in a defined space. Subsequently, the work of stabilizing the gravel layer is simulated by loading a cycling rod onto a sleeper located at the top 3 . Gravel shapes are formed by combining randomly generated discrete elements using the Delaunay triangulation function.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Suhr et al 20 and Vizcarra et al 21 also studied the compression performance, direct-shear performance and triaxial-shear performance of railway ballast by combining the physical tests with the DEM simulations. Guo et al 22 used the DEM to simulate the direct-shear performance of the mixture of ballast and rubber. The simulation results could be well matched with the test results in the laboratory, which verified the correctness of the parameters in the DEM modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al. 22 used the DEM to simulate the direct-shear performance of the mixture of ballast and rubber. The simulation results could be well matched with the test results in the laboratory, which verified the correctness of the parameters in the DEM modeling.…”
Section: Introductionmentioning
confidence: 99%